Determinants and outcomes of adherence to recommendations from a multidisciplinary tumour conference for hepatocellular carcinoma. Issue 11 (28th May 2014) - Gashin, Laurie; Tapper, Elliot; Babalola, Atinuke; Lai, Kuan‐Chi; Miksad, Rebecca; Malik, Raza; Cohen, Eric
Abstract: Background: The multidisciplinary tumour conference (MTC) represents the standard of care in the management of hepatocellular carcinoma (HCC). Clinical outcomes in relation to adherence and non‐adherence to MTC recommendations have not been studied. Methods: A total of 137 patients with HCC and cirrhosis whose cases were submitted to a first MTC discussion between 1 January 2009 and 31 December 2010 were identified. Clinical data, management recommendations, adherence, treatment regimens and overall survival were reviewed. Results: There were 419 MTC discussions on 137 patients with cirrhosis and HCC. The MTC recommendations made in 145 discussions on 90 separate patients were not followed. Patient‐related reasons for deviation from MTC recommendations included failure to attend for follow‐up ( n = 24, 16.6%), clinical deterioration ( n = 19, 13.1%) and patient preference ( n = 13, 9.0%). Physician‐related reasons for discordance included treating physician preference ( n = 43, 29.7%) and finding that the patient was not a candidate for the recommended intervention ( n = 37, 25.5%). After the first MTC discussion, 62.0% of patients received the recommended treatment; these patients were more likely to be alive at 1 year compared with those who did not receive the recommended treatment ( P = 0.007). More of the patients who followed recommendations underwent liver transplantation (25.6% versus 14.4%; P = 0.10). Conclusions: There are patient‐related as well as physician‐related reasons for non‐adherence to recommendations. Non‐adherence affects clinical outcomes and can be avoided in selected cases.